Discovery of novel dual-active 3-(4-(dimethylamino)phenyl)-7-aminoalcoxy-coumarin as potent and selective acetylcholinesterase inhibitor and antioxidant. (1st January 2019) - de Souza, Gabriela Alves; da Silva, Soraia John; Del Cistia, Catarina de Nigris; Pitasse-Santos, Paulo; Pires, Lucas de Oliveira; Passos, Yulli Moraes; Cordeiro, Yraima; Cardoso, Cristiane Martins; Castro, Rosane Nora; Sant'Anna, Carlos Mauricio R.; Kümmerle, Arthur Eugen
Abstract: A series of 3-substituted-7-aminoalcoxy-coumarin was designed and evaluated as cholinesterase inhibitors and antioxidants. All compounds were effective in inhibiting AChE with potencies in the nanomolar range. The 3-(4-(dimethylamino)phenyl)-7-aminoethoxy-coumarin (6a ) was considered a hit, showing good AChE inhibition potency (IC50 = 20 nM) and selectivity (IC50 BuChE/AChE = 354), quite similar to the reference drug donepezil (IC50 = 6 nM; IC50 BuChE/AChE = 365), also presenting antioxidant properties, low citotoxicity and good-predicted ADMET properties. The mode of action (mixed-type) and SAR analysis for this series of compounds were described by means of kinetic and molecular modeling evaluations. Graphical Abstract: